Keeping up with the Novaks? Income distribution as a determinant of household debt in CESEE - Mariya Hake; Philipp Poyntner (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
This paper constitutes an initial attempt to shed light on the role of income distribution in household debt and financial market access in Central, Eastern and Southeastern Europe (CESEE). Using household-level data from the OeNB's Euro Survey for the period 2009-2018, we address the question whether interpersonal comparisons ("keeping up with the CESEE Joneses" i.e. "the Novaks") affect the probability of having and planning a loan. Applying multilevel probit modeling to take into account the hierarchical structure of the data, our results support the notion that higher income inequality is negatively correlated with the probability of having a loan at the bottom of the distribution, and positively at the top. We show this impact for almost all components of household debt, but evidence is strongest for mortgage, car and foreign currency loans. Interpersonal comparisons turn out to drive loan intentions, however, mainly on the very top of the income distribution.
URN:NBN:fi:bof-202002131058
Keywords: G0; D1; D3; 330; household loans; relative income; income distribution; multilevel models; CESEE